Structural, physicochemical and anticancer study of Zn complexes with pyridyl-based thiazolyl-hydrazones - UĞUZ NELİ, ÖZLEM; KOCA, ATIF (My University, 2023)
Thiazolyl-hydrazones (THs) exhibit a wide spectrum of biological activity that can be enhanced by complexation with various metal ions. Zn(II) complexes with α-pyridine-1,3-TH ligands may represent an alternative to the standard platinum-based chemotherapeutics. In addition, they show photoluminescence properties and thus can be regarded as multifunctional materials. In this study, we synthesized and characterized three neutral Zn(II) complexes (1–3) with pyridine-based TH ligands HLS1‒3 in order to investigate the influence of the ligands charge on the structure and intermolecular interactions in the solid state, and consequently photophysical properties. The deprotonation of the ligands mainly affects the relative energies of electronic levels in the complexes, compared to cationic counterparts, resulting in similar photoluminescence mechanisms and quantum yields with a small shift in emission energy. The influence of the substitution at the ligands’ periphery on the selected quantum molecular descriptors of the complexes is localized to the substitution site. Also, the substituents did not considerably influence the redox responses of the complexes. However, predominant spectral changes were observed in the course of the first reduction and oxidation processes which caused distinct spectral color changes indicating their possible functionality for electrochromic applications. In addition, complex 1 showed antiproliferative activity with GI50 values below 2 µM on all tested cancer cell lines.
Keywords: Kimya; Analitik Kimya; Biyokimya; Biyoinorganik Kimya; Fizikokimya; Spektroskopi; İnorganik Kimya; Temel Bilimler; Chemistry; Analytical Chemistry; Biochemistry; Bioinorganic Chemistry; Physical Chemistry; Spectroscopy; Inorganic Chemistry; Natural Sciences; Temel Bilimler (SCI); KİMYA, İNORGANİK VE NÜKLEER; KİMYA, ANALİTİK; SPEKTROSKOPİ; KİMYA, ORGANİK; Natural Sciences (SCI); CHEMISTRY; CHEMISTRY, INORGANIC & NUCLEAR; CHEMISTRY, ANALYTICAL; SPECTROSCOPY; CHEMISTRY, ORGANIC; Fizik Bilimleri; Organik Kimya; İnorganik kimya; Physical Sciences; Organic Chemistry; Anticancer activity; Intermolecular interactions; Photoluminescence; Spectroelectrochemistry; TD-DFT